A Study on the Nature of Context from the Perspective of Islamic Jurisprudence and Usul al-Fiqh - ????? ?????, ????; ?????, ???????; ?????, ???? (??? ? ????)
Context, as the mental framework and format of speech and the place where evidences are realized, plays a role in understanding the intention of speech and is arranged in the form of either previous or future attached and connected verbal evidences. Detached evidences are considered as attached evidences if applied in the speech of a speaker like the divine lawgiver whose habit is to apply evidences separately and rely on them; hence, attachment in his words constitutes detachment. Textual evidence, due to its closeness and connection to the speech, is considered as attached evidence; even one may say the former is of the latter?s type or identical to it. The intention and termination of the speech, although helpful as an essential element in this regard, lack the necessary capacity to be included into the definition, since they fail to cover all instances of context conveyance including instances not intended by the speaker such as implicit conveyance. In addition, a definition of context which does not include previous verbal evidences or contextual evidences is a strict definition which is in contrast with its wide cases of application. On the other hand, consideration of detached evidences in all speeches even in the divine lawgiver's is an extended and defective definition of context.